Stereoselective synthesis of Heliannuol G. Issue 46 (15th November 2017) - Sarkar, Debayan; Ghosh, Manoj Kumar
Graphical abstract: Highlights: First stereoselective synthesis of Heliannuol G is reported. o -Quinone methide intermediate as a key step is proposed. Impressive overall yield of 12.37% in linear 7 steps. The synthesis supports that the structural revision done by Shishido group. The present synthesis triumphs over all the drawbacks associated with earlier synthesis. Abstract: The first stereoselective synthesis of Heliannuol G has been achieved employing an o -quinone methide intermediate. The present synthesis triumphs over all the drawbacks associated with the reported one and reveals an impressive overall yield of 12.37%.